Damage analysis of aluminum alloy gusset joints under cyclic loading based on continuum damage mechanics. (1st October 2021) - Liu, Hongbo; Li, Bohan; Chen, Zhihua; Ouyang, Yuanwen
Highlights: A damage-coupled constitutive model of 6061-T6 aluminum alloy was established. Low-cycle fatigue experiments of aluminum alloy gusset joints were performed. Damage distribution at the moment when failure occurred was obtained by simulation. Abstract: Owing to their advantageous properties, such as light weight, high strength, and good corrosion resistance, aluminum alloys have been widely used for structures in environments subject to corrosion, such as coastal environments and swimming pools. However, compared to steel, aluminum alloys have a lower elastic modulus and thus are more flexible and sensitive to cyclic loads, such as wind loads, and low cycle fatigue failure due to damage accumulation. In this study, we performed hysteretic experiments and low-cycle fatigue experiments to investigate the damage characteristics, including the failure modes, hysteretic curves, and fatigue life, of aluminum alloy gusset joints under cyclic loads. Then, we established a damage-coupled cyclic plastic constitutive model of 6061-T6 aluminum alloy based on continuum damage mechanics and implemented it in ABAQUS through a user-defined material model subroutine (UMAT). The parameters of the constitutive model were determined from cyclic uniaxial tests, and using the subroutine, a numerical simulation of the joints was carried out. The simulation results of the damage distribution, hysteretic curves, and fatigue life of the joints are consistent with the experimental results, which confirm that the analysis method established in this study can predict the crack location effectively. Due to the small number of experimental joints, the prediction of fatigue life needs further research to improve the reliability.